Endosymbiotic Ciliated Protozoan Biota of Dromedary Camels and Domestic Cattle in Tunisia - Gürelli̇, Gözde; Daw, Ali Fouze Othman Elhadi (Zootaxa, 2020)
Species concentration and composition of endosymbiotic ciliates were investigated in the forestomach contents of 12 dromedary camels (Camelus dromedarius) and the ruminal contents of 16 domestic cattle (Bos taurus taurus) living in Ben Gardane, Tunisia. Sixteen species and 8 morphotypes, belonging to 8 genera, were identified from dromedary camels, and 18 species and 13 morphotypes, belonging to 8 genera, were identified from domestic cattle. This is the first report on the endosymbiotic ciliated protozoan biota of dromedary camels and cattle living in Tunisia. The mean density (± SD) of ciliates in the forestomach samples of dromedary camels and the ruminal samples of domestic cattle was 65.4 ± 69.4 × 104 cells mL–1 and 54.2 ± 55.8 × 104 cells mL–1, respectively. Diplodinium cameli and Blepharoconus krugerensis were detected for the first and second time, respectively, from the ruminal contents of cattle. Caloscolex camelinus and B. krugerensis were studied in detail with a scanning electron microscope.